Authentic leadership revisited : an empirical study of morality in authentic leadership - Bartsch, Marvin (2018)
Answering to recent calls in literature to reconsider the necessity of morality in the concept of authentic leadership, the purpose of this work was to empirically evaluate the role of morality inside the construct. To do so, a survey experiment was created that examines the effects of the two concepts of authenticity and morality on perceived leader effectiveness. Most importantly the results of the experiment have shown that there is an insignificant difference between inauthentic but moral leaders and authentic but immoral leaders in perceived leader effectiveness. Ultimately, the findings suggest that immoral leaders should not be generally excluded from authentic leadership constructs and that the concept should be subject to further investigation.